Explaining Consumer Reactions to Corporate Social Responsibility: The Role of Gratitude and Altruistic Values - Romani, Simona; Grappi, Silvia; Bagozzi, Richard P. 1946- (2013)
Although a lot of research establishes consumer reactions to corporate social responsibility (CSR), little is known about the theoretical mechanisms for these reactions. We conduct a field experiment with adult consumers to test the hypothesis that the effects of perceived CSR on consumer reactions are mediated by felt gratitude and moderated by the magnitude of altruistic values held by consumers. Two classes of consumer reactions are considered: intentions to (1) say positive things about the company, and (2) participate in advocacy actions benefiting the company.
Keywords: Consumer behavior; Altruistic values; Gratitude; Corporate Social Responsibility